Neutrophil Extracellular Traps Mechanisms and Role in Health and Disease - Anders, Hans-Joachim; Mulay, Shrikant R. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Neutrophils regulate immune responses during homeostasis as well as disease pathogenesis. Especially, the neutrophils extracellular traps largely contribute to necroinflammation. This book highlights the role of neutrophils and neutrophils extracellular traps in various sterile and non-sterile, acute and chronic inflammatory conditions affecting both human and animal health.